Investigation of the interaction between two phenylethanoid glycosides and bovine serum albumin by spectroscopic methods - Ai-Zhi Wu; Chao-Zhan Lin; Ya-Jing Zhai; Jia-Lin Zhuo; Chen-Chen Zhu (Elsevier, 2013)
Two phenylethanoid glycosides, acteoside and forsythoside B, were first isolated from the traditional Chinese herb Callicarpa peii H.T. Chang. The interaction between the two phenylethanoid glycosides and bovine serum albumin (BSA) was investigated by fluorescence, UVâvis absorbance and circular dichroism (CD). The results showed that the quenching mechanism in the drugâBSA binary systems was a combination of static quenching and non-radiative energy transfer. Displacement experiments confirmed that the drug bound to the site I of BSA. UVâvis and CD measurements indicated that the binding of the drug to BSA induced conformational changes in BSA. Keywords: Phenylethanoid glycosides, BSA, Fluorescence quenching, Site competitive binding